P0479 Population-based evidence that copy number alterations predict progression from low-grade dysplasia to advanced neoplasia in inflammatory bowel disease - J W Andersen; F S Troelsen; K Krogh; K Stribolt; T Graham; K Braeutigam; A Hart; A K Dige (Journal of Crohn’s and Colitis, 2026)
Abstract Background Low-grade dysplasia (LGD) is a key risk factor for the development of advanced neoplasia, i.e. high-grade dysplasia and colorectal cancer, in individuals with inflammatory bowel disease (IBD).1 Detection of LGD informs clinical decision-making, often leading to intensified surveillance or, in some cases, colectomy.2 Although several risk factors for progression have been identified, individual risk assessment remains challenging; thus, predictive tools would be of considerable clinical value. Copy number alterations (CNAs) have recently shown promise in this context.3 We therefore aimed to investigate whether CNAs in LGD tissue could predict progression to advanced neoplasia in a non-specialised, population-based setting. Methods We conducted a case-control study in the Central Denmark Region. Using national healthcare registries, we identified 53 individuals with IBD diagnosed between 1994 and 2018 who had a first-time episode of LGD that subsequently progressed to advanced neoplasia, with progression data available through 2023. Cases were matched 1:2 with controls based on age, sex, and follow-up time. DNA was extracted from pathologist-confirmed LGD lesions, followed by low-coverage whole-genome sequencing and copy number analysis. Cox regression analysis was used to evaluate copy number alterations, measured as the proportion of the genome altered (PGA), as predictors of progression to advanced neoplasia. Results Matching was successful, with comparable age, sex, follow-up time, IBD subtype distribution, and disease duration prior to LGD between cases and controls. The overall mean age was 62.0 years; 46.7% were female; 71.7% had ulcerative colitis, 20.6% Crohn’s disease, and 7.7% IBD-unclassified; the mean duration of IBD prior to LGD was 6.5 years; and the average follow-up was 6.4 years. Copy number alterations were more pronounced among cases, with a mean PGA of 11.6 (95% confidence interval [CI]: 8.5 -14.8) versus 4.82 (95% CI: 3.6-6.0) in controls. Individuals in the highest and second-highest PGA strata were more likely to progress, with hazard ratios (HRs) of 6.8 (95% CI: 2.4-19.7) and 3.7 (95% CI: 1.3-11.0), respectively, compared with the lowest stratum (PGA=0) (Figure 1). Conclusion In IBD patients with LGD, a higher burden of copy number alterations in the dysplastic tissue was strongly associated with progression to advanced neoplasia, indicating that CNAs may help stratify individual risk, even in a population-based setting. References: 1. De Jong ME, Van Tilburg SB, Nissen LHC, et al. Long-term Risk of Advanced Neoplasia After Colonic Low-grade Dysplasia in Patients With Inflammatory Bowel Disease: A Nationwide Cohort Study. J Crohns Colitis. 2019;13(12):1485-1491. doi:10.1093/ecco-jcc/jjz114 Gut. Published online April 30, 2025:gutjnl-2025-335023. doi:10.1136/gutjnl-2025-335023Gut. Published online January 29, 2025:gutjnl-2024-333353. doi:10.1136/gutjnl-2024-333353 2. East JE, Gordon M, Nigam GB, et al. British Society of Gastroenterology guidelines on colorectal surveillance in inflammatory bowel disease. Gut. Published online April 30, 2025:gutjnl-2025-335023. doi:10.1136/gutjnl-2025-335023 3. Al Bakir I, Curtius K, Cresswell GD, et al. Low-coverage whole genome sequencing of low-grade dysplasia strongly predicts advanced neoplasia risk in ulcerative colitis. Gut. Published online January 29, 2025:gutjnl-2024-333353. doi:10.1136/gutjnl-2024-333353 Conflict of interest: Dr. Andersen, Jesper Winkler: No conflict of interest Troelsen, Frederikke Schønfeldt: No conflict of interest Krogh, Klaus: No conflict of interest Stribolt, Katrine: No conflict of interest Graham, Trevor: No conflict of interest Braeutigam, Konstantin: No conflict of interest Hart, Ailsa: No conflict of interest Dige, Anders Kirch: No conflict of interest